2001
DOI: 10.1590/s0074-02762001000900021
|View full text |Cite
|
Sign up to set email alerts
|

Schistosomiasis mansoni is asssociated with pyogenic liver abscesses in the state of Minas Gerais, Brazil

Abstract: The association between pyogenic liver abscesses and schistosomiasis has been confirmed by clinical and experimental studies. In

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 9 publications
1
8
0
Order By: Relevance
“…17,18 Other investigators have reported a relationship between S. mansoni infection and pyogenic liver abscesses caused by S. aureus in experimentally infected mice and in humans. 19,20 These findings may also relate pelvic abscesses and shistosomiasis in our patient.…”
Section: Discussionsupporting
confidence: 60%
“…17,18 Other investigators have reported a relationship between S. mansoni infection and pyogenic liver abscesses caused by S. aureus in experimentally infected mice and in humans. 19,20 These findings may also relate pelvic abscesses and shistosomiasis in our patient.…”
Section: Discussionsupporting
confidence: 60%
“…The presence of granulomas produced by adult trematodes, their eggs or even their remnants in the liver portal triads act as foci for colonization of Staphylococcus species, which in the presence of staphylococcal bactermia might be implicated in the formation of pyogenic liver abscesses (Teixeira et al, 1996;Teixeira et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of hepatic abscesses is caused by the highly virulent methicillin-resistant Staphylococci/CA-MRSA, which can cause liver abscesses also in previously healthy adult individuals and in children. PLA caused by Staphylococcus aureus seems to be more common in patients with schistosomiasis (Teixeira et al 2001). An association between schistosomiasis and Salmonella infection is also well documented .…”
Section: Pla Caused By Other Bacteriamentioning
confidence: 99%